Russian Post-Soviet Folklore: Modern Oral Folk Stories about Merchants - Grakhova, Svetlana Ivanovna; Zakharova, Irina Mikhailovna; Okisheva, Karina Anatolevna; Gayfutdinova, Tatyana Viktorovna (Journal of History Culture and Art Research, 2020)
The verbal genres are of great importance in the oral lore of any nation. Nowadays more and more attention is drawn to popular stories of the past, of people who lived long ago, and so on. This article focuses on the stories about merchants that are classified as memorates (precursors of legend) and chronicles. The perception and image of merchants in the narratives under consideration are of particular interest. Modern storytellers show the representatives of the merchant class as creative people of great soul, deep faith, and high morals rather than money-grubbers. The verbal story is characterized by narrators’ striving to describe the events, preserving the factual authenticity. Like any folk text, an oral story is a collective genre: it is orally transmitted, it has variations, i.e. each storyteller participates in its creating and existing in their own way. Although there are text variants, the main storyline usually does not vary in oral narratives. Thus, modern oral stories about representatives of the merchant class of the past times do not break with the tradition that is an attribute of folklore. That gives grounds for arguing that such a thematic type of oral narrative as a story about merchants is independent. The independent position of the genre under study is also proved by its attributes that distinguish it from other types of folk prose. The article discusses the genre characteristics of oral stories about merchants, gives their thematic classification, and explains the style features. The texts have significant potential for historical reconstructing the persons and events associated with a particular region. They also reflect the general trends in Russian literature – to avoid a one-sided view on the past, to perceive and understand everything from the standpoint of truth, goodness, and beauty. In addition, the authors of the article focus on the issue of naming characters in oral stories about merchants. The role of the storyteller (narrator) as a subject of naming activity, as well as general mechanisms of character naming, is also shown. Naming the characters is presented as a process determined by the genre features of the folk stories under study, the corresponding ways and techniques of depicting reality.